POSSIBILITY OF IMPROVEMENT QUALITY OF FRUITS AND YIELD OF DATE PALMS CV. BRAIM USING SPRAY OF NAPHTHALENE ACETIC ACID AND POTASSIUM SULPHATE - I. A. Rashid; Th. H. R. Al-Falahy (مجلة الأنبار للعلوم الزراعية, 2025)
The research study was performed at the station of horticulture located in Latifiya region, for exploring possibility improving the physiochemical features of palms fruits cv. Braim with age 28 years, by spraying naphthalene acetic acid (NAA) at 0, 50, and 100 mg L-1  and potassium sulphate(K2SO4) at concentrations of 0, 15, and 20 g L-1, this was done three times after pollination, i.e., during the hababuk phase, onset of the kimri phase, and starting of the break green color phase. Results indicated that NAA spraying, especially at high concentration, boosted fruit weight and bunch weight, yield, moisture content, acidity, and reducing fruit drop, fruit ripening, dry matter content, total sugars, monosaccharide, disaccharide, and TSS which reached (10.76g, 11.60kg bunch-1, 92.81 kg palm-1, 44.67 %,0.252%,7.82%, 50.43%, 55.33%, 40.99%,22.68%, 18.30% and 47.62%). In the same context, potassium sulphate, especially at concentration of 20 g L-1, led to enhanced all physical and chemical traits while reducing fruit drop and acidity which gave (10.63g, 11.21 kg bunch-1, 89.68 kg palm-1, 41.32% and8.25% and 0.213%) compared with control. Furthermore, the interaction between the studied factors followed the same direction, NAA at concentration 100 mg L-1 plus 20 g L-1, attained the greatest possible values for weight of fruit and bunch, yield, and minimizing fruit maturation and dropping which gave (11.06 g, 12.23kg bunch-1, 97.88 kg palm-1, 51.12% and 8%) compared to control treatment